A QUALITATIVE STUDY OF CONSUMER PERCEPTION ON EMOTIONAL BRANDING OF STARBUCKS MANADO TOWN SQUARE - Senduk, Ayleen Tania; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Emotional branding is defined as the engagement of consumers in a deep, long-term, intimate emotional connection with the brand, which is beyond the benefit based satisfaction, and which creates a special trust based relationship for the development of a holistic emotional experience. The aim of this study is to know how is the Consumer Perception of Emotional Branding at Starbucks in Manado Town Square. In order to achieve these objectives the researcher got information from 15 informants using qualitative study which is in-depth interview and uses purposive sampling. The results showed the good emotional branding comes because of all the good exeperiences consumer gets when they visit starbucks coffee shop. In this case most of the consumer concern only on the service, price, product and the ambience. After made the conclusion of this current research,Â  it is better for consumer to know and explore about the thing that makes them have a emotional branding towards starbucks coffee shop. For the Starbucks Coffee Shop at Manado Town Square, it is more better to keep improving the service and always provide a good innovation to make customer stay and retain.Â Keywords: consumer perception, emotional branding, starbucks.